Comparative Effects of ADP and Thrombin in Producing Stasis Thrombosis - Stuart, R. K; Thomas, D. P (Thrombosis and Haemostasis, 1967)
1. The effect of intravenous ADP on the platelet count, whole blood clotting time and stasis thrombosis formation was investigated in rabbits.2. 20 μ/kg and 10 mg/kg of ADP produced, respectively, a moderate and marked reduction in the circulating platelet count.3. Both the low and high doses of ADP resulted in only a relatively slight shortening of the whole blood clotting time.4. Neither dose of ADP resulted in thrombus formation in isolated venous segments after 30 min of stasis.5. It is concluded that ADP alone is unlikely to be an initiating factor in the pathogenesis of stasis thrombosis.